A 24-Year-Old Male with Gigantism, Growth Hormone Deficiency, Suspected Clivus Chordoma, Primary Hypothyroidism, Hypogonadism and Pancytopenia - W.A. Arsana; M.I. Diah Pramudianti (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Pituitary gigantism is a condition caused by excessive secretion of Growth Hormone (GH). The GH is the most common pituitary hormone-deficient in pituitary disease. Chordoma is a bone primary tumor that grows slowly and is rarely found. Hypothyroidism is a pathological condition due to thyroid hormone deficiency. Symptoms of hypogonadism are non-specific including libido disorders, erectile dysfunction, and decreased muscle mass and no hair growth in the head or body. A 24-year-old male came with pain in the knee. Physical examination showed increased growth of natural and body parts as well as the loss of body hair. Laboratory investigations revealed pancytopenia, increased prolactin; decreased GH, Insulin-Like Growth Factor-1 (IGF-1) and testosterone; increased Thyroid-Stimulating Hormone (TSH), decreased Free Triiodothyronine (FT3) and Free Thyroxine (FT4). Ahead MRI demonstrated the presence of a mass in the clivus. In this case, the patient presented with clinical gigantism. However, laboratory examination showed decreased GH and IGF-1, which might be due to the suppressive effect of mass on the clivus bone to the pituitary. Further examinations were needed to clear the suspicion of hypothyroid. Hypogonadism can result from suppression in the pituitary. Pancytopenia can be caused by a deficiency of GH or from hypothyroidism. Gigantism may occur with GH and IGF-1 deficiency due to suppressed pituitary caused by chordoma.